Semi-segmented lumbar supernumerary hemivertebra resection in congenital scoliosis: a case report - Bianca Mihaescu; Ecaterina Maria Sora; Ana Manu; Vlad Pencea; Stefan Gavriliu (Journal of Medical Case Reports)
Abstract Background Congenital scoliosis with progressive potential is a controversial subject in early-onset spinal deformities. The presence of a hemivertebra may produce severe spinal deformities. The evolution of a scoliotic curve in these cases is unpredictable and requires careful follow-up dependent on multiple variables, such as the location of the hemivertebra, the age of the patient at the time of diagnosis, and the degree of deformity already present in both sagittal and frontal planes. A segmented hemivertebra is an obvious cause of spinal deformity owing to its high progressive potential. A semi-segmented hemivertebra may induce severe deformities and surgery may be required, depending on the patients’ age, current deformity, and progressive potential. The age of 1.5–6 years is ideal to obtain an excellent surgical result. Prophylaxis of a predicted severe scoliotic curve owing to a semi-segmented hemivertebra requires a strategic surgical approach. While there are multiple surgical treatment options available nowadays, the current gold standard is the resection of the hemivertebra via a single posterior approach with limited fusion. Case description A 5-year-old Caucasian male child with congenital scoliosis owing to a semi-segmented hemivertebra at the thoracolumbar junction and a synchondrotic vertebral body bridge below the hemivertebra. The particularity of the hemivertebra consisted in the fact that it involved the L1 thoracolumbar transition area. The architecture of the upper part of the deformity resembled a T12-like deformity while the lower part was L1-like. Hemivertebra resection was performed by posterior approach and a short segmental fusion. The complete resection of the hemivertebra corrected the scoliotic curve and improved spinal balance. The patient was allowed to ambulate independently 3 days postoperatively while wearing a protective brace. Unrestricted daily activity was permitted 3 months after surgery. No complications were noticed until now. Conclusion Extensive clinical and imaging examination of the congenital malformation should be performed in all cases of congenital scoliosis owing to semi-segmented hemivertebra, especially if surgery will be performed. Proper diagnosis, age at surgery, and appropriate surgical technique ensure good results. Establishing which part of the involved spinal segment, including the semi-segmented hemivertebra, must be resected is essential to obtain a good correction with the shortest possible spinal fixation.